Self-Perceived TPACK of Public Secondary English Teachers: Basis for an Extension Program - Lyzyl Lopez-Banuag (Future Science / FSH-PH Publications, 2026)
The need for quality education was the fourth sustainable development goal of UNESCO which ensured inclusive, equitable, and lifelong learning opportunities for all learners. Its implication to increasing the supply of qualified teachers in developing countries was part of the major roles of teacher education institutions. Through complete enumeration, this study examined the self-perceived technological pedagogical and content knowledge of junior and senior high school English teachers in a large public school for S.Y. 2024-2025. It further aimed to design an extension training program for implementation in the research locale. After a series of preliminaries including the online orientation and obtaining informed consent in person, an adopted and validated survey questionnaire was administered in Google form in a group chat. Statistical information analyzed through the computation of weight and mean revealed that the respondents are generally competent to very much competent in terms of TPACK. There were suggested learning objectives, activities, and materials applicable and purposeful for an extension program designed to enhance the competence of the faculty recipients in integrating technology in both online and classroom-based teaching.